Enhancing ESL low proficiency pre-university students’ writing skills through flipped writing framework - Lee, Rebecca Su Ping; Verezub, Elena; Ida Fatimawati Adi Badiozaman (Penerbit Universiti Kebangsaan Malaysia, 2024)
The flipped classroom model, which aims to foster learners' prior knowledge through online or offline platforms outside of class, thereby reserving in-class time for more interactive and collaborative learning, represents a significant pedagogical advancement, particularly in tertiary education especially during and post-pandemic. Despite extensive research into the efficacy of flipped learning in enhancing proficiency among English as a Second Language (ESL) learners across various domains, few studies have specifically addressed the enhancement of writing skills among low-proficiency ESL pre-university students through product-genre based flipped learning. Therefore, this study seeks to evaluate the impact of a product-genre based flipped classroom on academic writing (process writing) performance among low-proficiency ESL students, and to develop a tailored flipped learning framework for ESL students at the pre-university level. Using an experimental design, the study compared traditional writing instruction in a control group with flipped classroom methods in an experimental group. Quantitative analysis yielded two significant findings: firstly, students' writing performance showed a marked improvement from pre-test to post-test when using the flipped classroom model; secondly, a positive correlation emerged between product-genre based flipped learning and writing performance. This study enriches the literature by providing empirical evidence of how product-genre based flipped learning can enhance writing skills among low-proficiency ESL students. It also introduces a novel flipped writing framework tailored specifically for ESL pre-university students, offering educators a valuable resource for designing effective writing activities in this educational context.